Progenies selection F4 from icatu and catuaí amarelo crossing with resistance to rust - Cardoso, Diego Abreu; Mendes, Antonio Nazareno; Carvalho, Alex Mendonça; Lima, Amador Eduardo; Botelho, Cesar Elias; Carvalho, Gladyston Rodrigues; Dias, Rodrigo Elias (Coffee Science - ISSN 1984-3909, 2017)
We aimed at evaluate and select coffee tree progenies in F4 generation in order to obtain rust resistant cultivars and agronomic characteristics superior to traditional cultivars. This research was carried out with 33 progenies resulted from crossing of Icatu cultivars and Catuaí Amarelo IAC 62, IAC 17 and the progenies IAC 5002 and IAC 5010; and three susceptible controls. The experimental design used was a randomized block with four replicates with ten plants per plot. The coffee yield (sc.ha-1), percentage of grains retained in sieve “17 and above”, vegetative vigor, incidence and severity of rust were evaluated. The results indicated that the evaluated progenies exhibited variability for the caracteristics analysed. We conclude that the H 141-17-46 progenies Cova 8, H 41-26-48 Cova 14 and H 141-10-10 Cova 5 have the highest value of productivity and low incidence and severity of rust allied with high vegetative vigor, and the possibility of selecting outstanding progenies in the studied population.